ANALISIS SUKU BUNGA DAN NILAI TUKAR TERHADAP IMBAL HASIL SURAT UTANG NEGARA DI INDONESIA - Louhenapessy, Fredy H.; Ramly, Amin; Sapthu, Andre; Saptenno, Fibryano (Jurnal Cita Ekonomika, 2024)
This study aims to analyze the effect of interest rates, exchange rates and the consumer price index on the yield of Government Securities (SUN) in Indonesia from 2005 to 2023. This study uses multiple linear regression methods, this study examines the relationship between independent variables, namely interest rates, the exchange rate of the rupiah against the United States dollar and the CPI on the dependent variable, namely yield SUN. The results showed that interest rates have a positive but insignificant effect on SUN yield or are not strong enough to be considered significant in determining the overall SUN yield. The rupiah exchange rate has a negative but significant effect on SUN yield,where the depreciation of the rupiah against the dollar tends to increase yield as compensation for exchange rate risk.Meanwhile, CPI has a negative and insignificant effect on SUN yield, indicating that although an increase in CPI, which reflects inflation, tends to be followed by a decrease in SUN yield, its influence is not strong enough to be the main factor in determining yield. These findings provide important implications for policy makers and market participants in understanding the dynamics of the Indonesian bond market and in managing national financial stability.